The Ethical Aspects of Techno-Science, Dromology, and Hyperreality - Livia Sebikova (Communications - Scientific letters of the University of Zilina, 2018)
The contemporary societies are characterized by several attributes. We can talk about a postmodern, scientific-technical, information, fast, hyperreal or consumer society. In fact, these attributes do not appear in isolation, but in relation to each other. The author inspired by postmodernists such as Lyotard, Virilio, and Baudrillard, focuses on identifying the ethical aspects of these phenomena and deals with the contemporary image of man and societies in this context. Science, technology, information and communication technologies permeate all spheres of human being and change the nature of knowledge. Information, time and speed are important factors and manipulation with them is a key way of ordering societies and shaping the image of man. We may call this an ability to transform reality and create hyperreality. Hyperreality may also be referred to as the paradigm of the current cultural situation of consumerism.